Toward humanistic healthcare through dystopian visions: Sally Wiener Grotta’s “One Widow’s Healing” - Meeyoung Kang (Philosophy, Ethics, and Humanities in Medicine)
Abstract Background Critical medical humanities critique the traditional medical humanities’ focus on producing humane doctors, arguing that it plays only a supplementary role in medical education, and advocate for understanding health, disease, and humanity from a biocultural perspective. Essentially, they emphasize structural inequalities in modern medicine. Methods This study analyzes Sally Wiener Grotta’s “One Widow’s Healing” from the perspective of critical medical humanities. In line with this critical perspective, this study highlights the human alienation and oppression caused by biopower and technology-driven medicine in “One Widow’s Healing.” Results This story presents a dystopian vision of future healthcare systems in the highly technologically advanced and hyper-connected societies of 2100 and advocates for a reorientation of medicine toward a holistic, culturally informed practice that prioritizes human well-being and empathy. Conclusions By analyzing the literary response to the dystopian future, this study explores the potential dangers at the intersection of capitalism and technocentric healthcare, reflecting on the future direction of humanistic medicine.